Mantle-driven plate convergence due to slab detachment - Yangming Wu; Manuele Faccenda; Jie Liao; Jianke Fan; Feng Guo; Zhongping Lai (Communications Earth & Environment)
Abstract The coupling between the lithosphere and mantle dynamics is important for Earth’s tectonic movement and deformation. Plate driving forces changing from subduction to viscous flow drag can potentially explain the continuous plate convergence where subducting slabs are detached. However, tectonic expressions in different slab detachment scenarios are inconsistent and the role of mantle flow in plate convergence remains enigmatic. Through numerical modeling, we demonstrate that plate convergence can be caused by mantle flow induced by slab detachment and regulated by lithospheric mantle-ridge interaction. Spreading ridge-trench collision has minimal effects on the deformation of overriding plates, whereas continent-trench collision can lead to substantial tectonic uplift at suture zones. Mid-ocean ridges bounding incoming plates accelerate plate motion in ridge-trench collision scenarios and induce considerable tectonic uplift in continent-trench collision scenarios, as evidenced by the acceleration of the Farallon-Pacific ridge spreading and the rapid uplift of the Himalayas after slab detachment episodes.